The university as a site for transformation around sustainability. (2015) - Winter, Jennie; Cotton, Debby; Hopkinson, Peter; Grant, Vivien
Universities are increasingly being seen as key sites for transformation around sustainability. However, much of the literature in this area uses the terms transformation and transformative learning rather uncritically. Moreover, there is little extant research which has investigated the links between transformative learning theories and Education for Sustainability (EfS). This paper reports on a research project which explored academic and student perceptions of the opportunities for transformation around sustainability in two UK universities. The findings suggest that, despite shared understanding about the nature of pedagogic approaches that promote deep learning, academics are wary about promoting transformation beyond the professional sphere and students are more likely to have transformative experiences outside the formal curriculum. There are indications that although universities have significant potential as sites for transformation around sustainability, at present, this is not being achieved.